Wheels in Motion: Exploring Challenges and Opportunities in Motorsports Management in Nepal - Baral, Anil Kumar (Journal of Advanced Academic Research, 2024)
Nepal is a beautiful country with diverse terrain; Nepal's landscape consists of mainly three zones plain or terai, which occupy a quarter area of the country’s land this is almost surrounded by hills, which is around 40 per cent of the total area of the country. These hills are crowned by the majestic Himalayas including the world's highest peak Mount Sagarmatha (Mt.Everest )and other eight globally recognized mountains over 8000 meters. This unique backdrop of the country landscape gives enough trilling to motorsports events, including motorcycle, four-wheeler sports, and karting. The beautiful landscape of the country, where hill terrain is immediately accessible from the 5-10 km plain terai zone, (Plain Zone) along with beautiful scenes of mountains, lakes, rivers, and greenery, provides an ideal setting. The amazing fact is that when the riders reach the peak of the hills, not only the scenery will attract them but when they feel that the sky and stars are near to them and seem that they can be touched by their naked hand gives both pleasure, enjoyment and race emotion. We can assume Nepal as one of the best locations for the motorsports activities like touring. Additionally, the living cost is low, it is affordable for foreigners, and visitors, safety may be the other wonderful reason thus we can argue that Nepal is the best destination for motorsports tourism, presenting one of the main opportunities for the industry. To capitalize on the above potential, professionalism in event management is essential. Sometimes the traditional definitions of sports management may not work and redefining sports management may require however, traditional concerns of planning, budgeting, organizing, directing and ensuring profitability may need to be done for successful event execution in a country like Nepal. These are the functional areas that Sports managers perform. This article is the pathway to determine the challenges and opportunities in motorsports in Nepal. The findings are assumed to guide the Enthusiasts' club owners/managers and other concerned associates, they are engaged here in this article for their valuable inputs involving them in primary data collection. The Primary data are collected from clubs/ Motorsports Professionals national and international motorsports professionals to determine their major challenges. The importance of a disciplinary attitude among players is also highlighted. Primary data was collected through a questionnaire approach, and focus groups involving stakeholders such as clubs, federations, and provincial associations. The survey aimed to analyze the challenges and opportunities in motorsports management in Nepal. It has been observed that the Nepal Automobile Association (NASA-NEPAL) is the one and only Motorsports Federation, which is working in the development of motorsports in Nepal since its inception in 2008-09. It is affiliated with national and governmental regulating bodies like the Nepal Sports Council and international bodies like FIA, FIM, and CIK.  Around 10 national clubs are associated with NASA Nepal and seven Provincial level associations are actively collaborating with the National Federation where approximately 200 players 100 marshals and 100 sports volunteers are primarily engaged in Nepal. During Primary data collection and the focus group discussion, it is also observed that this organized structure provides governance, safeguarding players, providing officiating training, and managing volunteers. In the primary stage of the Nepal motorsports fraternity, Nepalese youth or we can say players are drawn towards motorsports through their enthusiasm and they can be symbolized as self-taught players. Now the scenario has changed second stage Players are now playing the game. Apart from these systematic governing bodies, some of the motorsports clubs are now working in professional and business modules; secondly, Government investments in infrastructure, like racetracks, further enhance opportunities in the motorsports sector in Nepal. However, multiple challenges remain, and we have tried to identify the maximum by the research. Some of the heart-touching and crucial challenges may be financial security for players to compete nationally and internationally, along with the limited involvement of national automobile businesses in event sponsorship. The absence of automobile manufacturers poses challenges in fundraising, but collaborations with numerous other sponsors remain viable in the nation. In conclusion, Nepal's motorsports scene holds immense promise, contingent upon addressing financial challenges and securing support from stakeholders. This article offers insights into the challenges and opportunities in motorsports management in Nepal, contributing to its potential on the global stage.